The awareness of property planning (wills and hibah) among mosque pilgrims Sultan Salahuddin Abdul Aziz Shah Mosque (MSSAAS), Shah Alam Selangor / Nurul Fatin Syahida Abdullah - Abdullah, Nurul Fatin Syahida (2019)
Property of inheritance is one of the properties of the heirs and it will result in a split between families. It will also result in the property becoming frozen because no heirs will manage the property. Wills is a statement which is made by someone wish after they die and the hibah is a statement made by someone wish during life. Wills and hibah is certain of the way to distribute the wealth without using the faraid system because it is much easier than the faraid system. This study is to know the awareness of the property planning among the mosque pilgrims that they are aware or not about the wills and hibah. Other than that, this study also to identify the level of understanding of property planning among mosque pilgrims of Sultan Salahuddin Abdul Aziz Shah which is the researcher want to know the level of understanding about the wills and hibah among the pilgrims. Therefore, the researcher also has a suggestion the solution how to attract Muslims to use wills and hibah among them which is the researcher want the Muslims know about the wills and hibah and apply in their life. Besides that, this study is using the quantitative method by using the survey questionnaire and the total of the questionnaire is 50 respondents has been answered by the mosque pilgrims